2022
DOI: 10.1007/s00223-021-00938-w
|View full text |Cite
|
Sign up to set email alerts
|

Newly Diagnosed Celiac Disease and Bone Health in Young Adults: A Systematic Literature Review

Abstract: Celiac disease (CD), a gluten-induced autoimmune disease, is associated with low bone mineral density (BMD) among children. Unfortunately, it is often diagnosed in adulthood, which may lead to an increased risk of fragile bones. The aim of this systematic review was to report on BMD status among young adults newly diagnosed with CD, and to examine the effect of a gluten-free diet (GFD), nutritional supplements, such as vitamin D, or antiresorptive medications on BMD recovery. Databases searched were Medline, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…A comparative meta-analysis of 20995 patients with CeD and 97777 controls from eight studies published between 2000 and 2007, found that patients with CeD have a 43% higher risk for developing non-traumatic fracture compared with controls[ 61 ]. Also a recent study found that patients with newly diagnosed CeD have low bone marrow density and this improves after initiation of GFD[ 62 ].…”
Section: Probable Indications For Screening For Cedmentioning
confidence: 99%
“…A comparative meta-analysis of 20995 patients with CeD and 97777 controls from eight studies published between 2000 and 2007, found that patients with CeD have a 43% higher risk for developing non-traumatic fracture compared with controls[ 61 ]. Also a recent study found that patients with newly diagnosed CeD have low bone marrow density and this improves after initiation of GFD[ 62 ].…”
Section: Probable Indications For Screening For Cedmentioning
confidence: 99%
“…Symptomatic disease may be associated with more significant bone mineral loss. Traditional risk factors are not always present, so young people, those with normal BMI and males can all be affected 104,105 . Bone fracture risk is increased in coeliac disease 15,106,107 with the risk persisting with ongoing villous atrophy.…”
Section: Monitoring For Complicationsmentioning
confidence: 99%
“…There is evidence to suggest that BMD increases during the one or two years up to 5 years of GFD, particularly in those younger than 40 years of age [ 26 , 27 , 77 , 79 ]. GFD benefits elderly patients with newly diagnosed CeD, with significant gains in BMD at the lumbar spine and femur in the first 12 months of treatment [ 78 , 80 ]. However, convincing evidence about achieving and maintaining normal bone mass is lacking.…”
Section: General Non-pharmacological Management Of Osteoporosis In Ad...mentioning
confidence: 99%